2007
DOI: 10.1254/jphs.fp0061376
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacies of a Dipeptidyl Peptidase IV Inhibitor and α-Glucosidase Inhibitors in Oral Carbohydrate and Meal Tolerance Tests and the Effects of Their Combination in Mice

Abstract: Abstract. E3024 (3-but-2-ynyl-5-methyl-2-piperazin-1-yl-3,5-dihydro-4H-imidazo [4,5-d]pyridazin-4-one tosylate) is a dipeptidyl peptidase IV (DPP-IV) inhibitor. Since the target of both DPP-IV inhibitors and α-glucosidase inhibitors is the lowering of postprandial hyperglycemia, we compared antihyperglycemic effects for E3024 and α-glucosidase inhibitors in various oral carbohydrate and meal tolerance tests using normal mice. In addition, we investigated the combination effects of E3024 and voglibose on blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…In this study, treatment with mangiferin alone improved glucose tolerance, and combination treatment with sitagliptin additively increased plasma GLP-1 and insulin levels. These results are consistent with those of Yamazaki et al [16], who first suggested the benefits of combining DPP4 inhibitor and α-glucosidase inhibitor for the efficient improvement of postprandial hyperglycemia.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, treatment with mangiferin alone improved glucose tolerance, and combination treatment with sitagliptin additively increased plasma GLP-1 and insulin levels. These results are consistent with those of Yamazaki et al [16], who first suggested the benefits of combining DPP4 inhibitor and α-glucosidase inhibitor for the efficient improvement of postprandial hyperglycemia.…”
Section: Discussionsupporting
confidence: 93%
“…HIT-T15 cells (between passages 75-80) were cultured in RPMI 1640 media containing 11.1 mM glucose with 10% fetal bovine serum (FBS), 100 U/ ml penicillin and 100 mg/ml streptomycin at 37°C, atmosphere 5% CO 2/ O 2 . Media was changed every 2 d and cells were subcultured every 5-6 d. HIT-T15 cells were seeded into 24-well plate at a density of 2ϫ10 5 Gyeonggi-Do 471-711, Korea. Received July 4, 2007; accepted August 10, 2007; published online September 5, 2007 Compound K (CK) is a major intestinal metabolite of ginsenosides derived from ginseng radix.…”
Section: Methodsmentioning
confidence: 99%
“…Having different classes of anti-diabetic drugs with their sites of action being different, accumulating evidences suggests that combination therapy using these agents may be highly effective in achieving and maintaining target blood glucose levels. [4][5][6] The root of ginseng has been used for remedies in traditional Chinese medicine. The pharmacological properties of ginseng are mainly attributed to ginsenosides, which are the active components found in the extracts of different species of ginseng.…”
mentioning
confidence: 99%
“…To evaluate the effect of the DPP4 (E3) vaccine on glucose metabolism, a meal tolerance test (MTT) was performed instead of a glucose tolerance test, as it was reported that the secretion of GLP-1 is more strongly induced by complex nutrients than by glucose (24). Male mice (8 wk of age; n = 6) immunized with the E3 vaccine and fed a normal diet showed no change in glucose and insulin levels compared with the KLH control mice ( Fig.…”
Section: Improvement In Insulin Resistance Following Dpp4 Vaccinationmentioning
confidence: 99%